Efficacy of Magnesium Sulphate to Prevent Arterial Pressure Increases During Laparoscopic Cholecystectomy (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Background: Carbon dioxide pneumoperitoneum (PP) for laparoscopic surgery increases arterialpressure and systemic vascular resistance, these vasopressor responses are likely to be due to increasedrelease of catecholamine. Magnesium is well known to inhibit catecholamine release and attenuatevasopressin stimulated vasoconstriction.Objectives: This study has been undertaken with a view to find out the efficacy of magnesium sulphateto prevent arterial pressure increases associated with carbon dioxide pneumoperitoneum (PP) in patientsundergoing laparoscopic cholecystectomy.Methods: Sixty patients, of either sex, 18 60 years of age, undergoing elective laparoscopic cholecystectomywere randomly allocated in one of the two group’s containing 30 patients each. Magnesium SulphateGroup “M” received magnesium sulphate 30 mg/kg intravenously as a bolus beforecarbon dioxidepneumoperitoneum (PP).A control Group “C” received same volume of normal salinebefore carbon dioxidepneumoperitoneum (PP).Results: Mean arterial pressure was significantly less throughout the period ofpneumoperitoneum inpatients of Group M. Intravenous labetalol was required in 46.66% (14out of 30) of the patients in groupC to control intraoperative hypertension and it was clinicallysignificant in comparison to group M.Conclusion: Our study concluded that intravenous Magnesium Sulphate administered before carbondioxide pneumoperitoneum (PP) attenuates arterial pressure increases during laparoscopiccholecystectomy effectively and provides better hemodynamic stability.JBSA 2018; 31(2): 82-87